Exploring the Role of the Microbiome in Atopic Dermatitis: A Longitudinal Metagenomic Analysis in India - Ramakhrisnand, Ramakhrisnand (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Atopic dermatitis (AD) is a chronic inflammatory skin condition with a complex etiology, influenced by both genetic and environmental factors. The skin microbiome plays a crucial role in maintaining skin health, and dysbiosis is frequently observed in AD. This longitudinal metagenomic study aimed to investigate the dynamics of the skin microbiome in Indian AD patients and explore its association with disease severity and clinical outcomes. Methods: A cohort of 50 AD patients and 30 healthy controls from diverse regions in India were enrolled. Skin microbiome samples were collected at baseline, 3 months, and 6 months. Metagenomic sequencing was performed to characterize the microbial communities. Clinical assessments, including SCORAD (Scoring Atopic Dermatitis) and patient-reported outcomes, were recorded. Results: Significant differences in microbial diversity and composition were observed between AD patients and healthy controls. AD patients exhibited reduced diversity and an overabundance of Staphylococcus aureus compared to controls. Longitudinal analysis revealed fluctuations in the microbiome associated with disease flares. Specific microbial taxa, such as Streptococcus and Corynebacterium, showed inverse correlations with disease severity. Conclusion: This study provides valuable insights into the skin microbiome dynamics in Indian AD patients. The findings highlight the potential role of the microbiome as a biomarker for disease severity and therapeutic targets. Further research is warranted to explore the functional implications of these microbial shifts and develop microbiome-based interventions for AD management.